A STUDY OF THE IMPACT OF PARENTING STYLES ON THE DECISION-MAKING ABILITIES OF HIGHER SECONDARY STUDENTS - Kaur, Shaminder; Sharma, Madhu (International Journal of Research -GRANTHAALAYAH, 2025)
In the present era, parenting styles play a crucial role in the development of students’ personality, behavior, and decision-making abilities. The decisions students make in their lives—such as educational, vocational, and social decisions—depend on their self-confidence, experiences, and family environment. Parents’ disciplinary, permissive, or neglectful styles directly or indirectly influence students’ thought processes and decision-making. The main objective of this study is to examine the impact of parenting styles on the decision-making abilities of higher secondary students. This study attempts to determine whether different parenting styles have a significant impact on students’ decision-making abilities.